Active Solidarity: Centering the Demands and Vision of the Black Lives Matter Movement in Teacher Education. (February 2018) - Mayorga, Edwin; Picower, Bree
In the era of Black Lives Matter (#BLM), urban teacher education does not exist in isolation. The White supremacist, neoliberal context that impacts all aspects of Black lives also serves to support antiblackness within the structures of teacher education. In this article, the authors, who are grounded in a race radical analytical and political framework, share a vision of what it means to be an urban teacher who actively understands and teaches in solidarity with #BLM. The authors unpack their theoretical framework and the vision of #BLM while examining the state of teacher education in this era of neoliberal multiculturalism. The authors contemplate what a race radical, #BLM-aligned, approach to urban teacher education might look like. The article concludes by addressing ways that teacher educators must be in active solidarity with the #BLM movement to better prepare teachers who understand that the lives of their students matter within and outside of their classrooms.